Pembelajaran matematika secara daring pada masa pandemi Covid-19: efektivitas pembelajaran daring di SMK Negeri 2 Tanah Putih - Aulia, Jannatul; Roza , Yenita; Maimunah, Maimunah (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2021)
During the Covid-19 pandemic, the learning process must be carried out online. During the implementation of learning, it is undeniable that there are many complaints from various parties, especially students who judge online learning to be less effective. This study is a qualitative research with a descriptive method that aims to provide an overview of the effectiveness of online-based mathematics learning carried out at SMKN 2 Tanah Putih during the Covid-19 pandemic. The data collection technique was carried out using a google form questionnaire